2009
DOI: 10.1007/s12053-008-9037-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency technologies for road vehicles

Abstract: A key message of the Fourth Assessment Report (AR4) of the Intergovernmental Panel on Climate Change is that improved energy efficiency is one of society's most important instruments for combating climate change. This article reviews a range of energy efficiency measures in the transportation sector as discussed in AR4 and assess their potentials for improving fuel efficiency. The primary focus is on light-duty vehicles because they represent the largest portion of world transport energy use and carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 10 publications
1
33
0
3
Order By: Relevance
“…These actions are often categorized as eco-driving (e.g., McKinnon, 2015) [119], vehicle efficiency (e.g., Kobayashi et al, 2009) [131], collaborative initiatives with other supply chain actors (e.g., Mason et al, 2007) [132] and actions spurred by government (e.g., Stelling, 2014) [133]. The study of Leonardi and Baumgartner (2004) [91] analyzed specific activities adopted by German haulers to reduce the CO 2 emissions.…”
Section: Articlesmentioning
confidence: 99%
“…These actions are often categorized as eco-driving (e.g., McKinnon, 2015) [119], vehicle efficiency (e.g., Kobayashi et al, 2009) [131], collaborative initiatives with other supply chain actors (e.g., Mason et al, 2007) [132] and actions spurred by government (e.g., Stelling, 2014) [133]. The study of Leonardi and Baumgartner (2004) [91] analyzed specific activities adopted by German haulers to reduce the CO 2 emissions.…”
Section: Articlesmentioning
confidence: 99%
“…Kobayashi et al [5] studied the relationship between weight and CO 2 emissions. They concluded that a 10% decrease in vehicle weight ensures 6-8% lower fuel usage.…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al [11], Bastani et al [12] and Mayyas et al [13] investigated fuel consumption and greenhouse gas emissions depending on the vehicle type and weight reduction. The results indicated that a 10% reduction in vehicle weight can result in a 6%-8% fuel economy improvement.…”
Section: Introductionmentioning
confidence: 99%